Demographic trends in average wages of workers in indonesian provinces - Iwan Henri Kusnadi; Tamaulina Br. Sembiring; Muammar Khaddafi; Wina Nurhayati; Sahrul Sahrul (Institute of Computer Science (IOCS), 2023)
The average wage of employees is a significant indicator of economic and social welfare in Indonesia. Rising worker wages can indicate economic growth and enhanced welfare, whereas falling worker wages can indicate economic problems and social unrest. The research urgency is visualizing the demographic trends of average worker wages demonstrates that statistical data visualization is a solution for presenting data from the Indonesian Central Bureau of Statistics on wages in a more appealing and understandable manner. Using Google Data Studio for data visualization in this study can facilitate the transformation of complex data into engaging graphs and diagrams that are simple to share with readers. This study's contribution is a visualization of the demographic trend of the average hourly wage of employees in Indonesian provinces from 2018 to 2022. Visualize outcomes The average wage of Indonesian laborers has increased and decreased over the past five years. In 2022, the province of DKI Jakarta has the greatest average wage of all provinces, amounting to 32,685 dollars. In 2018, the province of West Nusa Tenggara had the lowest average wage, which was 11,359 rupiah per month. The average wage of Indonesian employees with five years of experience is IDR 16,888 per hour